Role of inclusive school libraries for children with down syndrome - Ikrimah, Awalia Latifa Mayda; Johan, Riche Cynthia; Khoerunnisa, Lutfi; Hadiapurwa, Angga; Ardiansah, Ardiansah (Jurnal Kajian Informasi dan Perpustakaan, 2024)
The existence of libraries in inclusive schools is regulated in Indonesian legislation. Its management needs to be considered so that its existence can support each student with various special needs. This study aimed to identify the role of the library in helping to foster the speaking skills of students with Down syndrome (DS) with a qualitative approach and case study method. Data were collected through observation of one student with DS, interviews with one teacher in charge of the library, one class teacher, and one principal, and voice recording documentation from three informants. Triangulation data analysis was conducted to examine findings of data sources from observations and interviews, and reference documentation in the form of inclusive school library management standards. The inclusive school library provided collections of fiction, non-fiction, serial publications, and reference collections. Children with DS most often used fiction collections in the form of picture storybooks. The facilities and infrastructure of the inclusive school library are similar to school libraries in general. The predominant service provided and carried out by library staff – who are also teachers, is storytelling - telling stories from books chosen by students with DS to help develop an interest in reading and foster verbal communication. The library is used by teachers in learning activities, carrying out motor skills such as arranging books, thickening lines in books provided at school, playing on computer tablets, coloring, and developing cognitive abilities to recognize letters and connect letters; this helps foster speaking skills of students with DS.